Spatial Metaphors in Introductory Statements of Humanities and Stem Disciplines: A Case Study of English and Mechanical Engineering Departments (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
Advances in higher education, specifically in science and technology, have engendered a significant shift of interest from a mainly liberal arts curriculum to STEM-related fields of study, creating a rift in the value systems undergirding the two academic domains. One of the ways the disciplinary disparity is institutionally expressed is through the language used in describing the core values of these disciplines, specifically in the introductory statements of departments. Using the lens of spatial metaphor to consider how the language expresses distinct realities that align with the public perceptions of the disciplines, this paper examines the metaphorical framings in the introductory statements of two disciplines in three US research institutions, representing the humanities and STEM. It explores how such framings help to establish their core values and have facilitated the ascendancy of STEM in recent times. I argue that by understanding the metaphors underlying these statements, we can better understand how these fields create distinct representational frame for expressing and promoting their image. I conclude by offering practical implications of how understanding disciplines define and position themselves can improve the quality of higher education.